External factors, leverage, and banks’ performance: Does risk matter? - Edwin Agus Buniarto (Sebelas Maret Business Review, 2023)
This study aims to analyze the risk variables as an intervening factor between external factors and leverage on the financial performance of banking companies in the Indonesian Capital Market. In this study, 45 banking sector companies became the population. The sampling technique was purposive sampling, so the samples were 5 companies for 3 years. The data analysis technique in this study uses SmartPLS. The results show that the t-count coefficient is greater than the t-table, indicating a significant effect of external factors on risk in the company. There is no significant effect of leverage on risk with a t-count value smaller than the t-table. External factors significantly affect financial performance, with a coefficient value of t-count greater than t-table. There is a significant effect of leverage on financial performance, with a t-count coefficient value more significant than the t-table. The risk significantly affects financial performance, with a t-count coefficient value more significant than the t-table.